Colonic transit diagnostic test shows significant gastrointestinal hypomotility in clozapine-treated patients in comparison with subjects treated with other antipsychotics - Baptista, Trino; Carrizo, Edgardo; Fernandez, Erika; Connell, Lisette; Servigna, Mercedes; Parra, Agner; Quintero, Jesus; Pabón, Albis; Sandia, Ignacio; Uzcáteguid, Euderruh; Serrano, Ana; Pirela, Natacha; et al. (Schizophrenia research, 2015)
Constipation occurs in 25–60% of the subjects during administration of the antipsychotic drug (AP) clozapine (CLZ). We used a colonic transit diagnostic test that quantifies in a single abdominal X-ray the number of silver O-ring markers out of 25 units ingested five days before. The quantity of markers is directly proportional to the degree of gastrointestinal hypomotility, and elimination of over 80% of the markers is considered normal. The test was applied to three groups of AP-treated subjects for at least three consecutive months: CLZ alone (n=45), CLZ+Other APs (n=28), and Other APs (n=64). The number of remaining markers at day 5 (mean±S.D.) was significantly higher in the CLZ alone (10.8±10.6) and in the CLZ+Other APs (9.7±9.7) groups than in the Other AP group (4.5±6.7), Kruskal–Wallis test: p=0.004. No significant associations were found between the number of markers, age, AP dose and treatment duration. All subjects who passed <80% of markers – which approximately corresponds to the 60th percentile of marker elimination – showed a scattered marker distribution along the colon, thus suggesting colon inertia. In subjects with hypomotility, 38.5% of the CLZ group, 25% of the CLZ+Other APs group, and 25% of the Other APs group were negative for the Rome III clinical criteria of constipation, thus showing objective, not subjective, hypomotility. This study objectively confirms significant gastrointestinal hypomotility associated with CLZ administration.